Neillands, The Hundred Years War - McCarthy, Joseph (Teaching History: A Journal of Methods, 1993)
The Hundred Years War, a series of sporadic campaigns stretching over 116 years, is best organized in eight periods of conflict, four between 1337 and 1396, and four between 1396 and 1457. What ties these campaigns together and distinguishes them from other conflicts between France and England is their focus on the English king's claim to the French crown. The simple part of dealing with them is the descriptive military narration, the complex part is tracing the familial and diplomatic circumstances shaping the alliances and motivations of the participants. Neillands does well enough with the former, not nearly as well with the latter.